The Role of Concern for The Environment and Perceived Consumer Effectiveness on Investors’ Willingness to Invest in Environmentally-Friendly Firms - Boey Huey Ming; Gerald Goh Guan Gan; Suganthi Ramasamy (Kajian Malaysia, 2015)
With a growing awareness on the need to provide better care for the environment, there is a greater need to understand the factors that facilitate environmentally-sustainable behaviour among the populace. Various researchers have studied factors influencing investors' willingness to invest in the past. This study however covers a segment of finance research, specifically behavioural finance as it examines investors' perceived consumer effectiveness (PCE). Specifically, this study examines the role of investor behaviour on corporate environmental strategies, which is relatively an underexplored field of study. This study contributes to the theme of sustainable development, more precisely, sustainable finance. The study of sustainable finance has become the attention of investors around the world and this study aims to analyse whether this sector of investment (green companies) will interest investors. It is proposed that consumers' concern towards the environment and perceived consumer effectiveness are significant predictors of investors' willingness to invest in the shares of environmentally-friendly firms in Malaysia. An understanding of the role of concern for the environment and perceived consumer effectiveness on investors' willingness to invest in environmentally-friendly firms will be useful to the government and NGOs in the formulation of policies that would encourage investment in firms that are sensitive towards the needs of the environment.